What are the prerequisites for a euro-area fiscal capacity? - Maria Demertzis; Guntram B. Wolff (Bruegel, 2016)
A monetary union without fiscal union is generally considered to be incomplete. We consider three steps for increasing the centralisation of fiscal functions, and discuss the prerequisites for moving forward at each one. Above all, fiscal integration is a matter of trust, which is currently at a low level. The first step would be to complete banking union and establish a more credible no-bailout clause. The conditions for addressing the fiscal dimensions of banking union are a denationalisation of the banking policy framework - including as regards exposure to sovereign debt - addressing non-performing loans and legitimising the fiscal backstop. The second step would move on from the first by adding funds for public goods and investment in the EU. With these, this step would create a re-insurance framework to help euro-area countries absorb large shocks. We consider a review of the EU budget and additional resources as conditions for this scenario. A system of check and balances is important. Last, we consider structural convergence to better deal with shocks as an essential prerequisite for mechanisms to cope with large country-specific shocks. The last step constitutes our analytical benchmark as it would move substantial government spending to the central level. This would allow euro-area fiscal stabilisation to be fully centralised. To enable this scenario, real economic differences between countries need to be lower, and a proper political union would need to be established, with legitimacy and a level of political integration very different from the situation today.
Keywords: 330